Dasysiphonia japonica - Kakkonen, Jenni E.; Worsfold, Tim M.; Ashelby, Christopher W.; Taylor, Andrea; Beaton, Katy (Zenodo, 2018)
(4) Dasysiphonia japonica (Yendo) H.- S. Kim, 2012 Status in U.K. – non-native. The filamentous red alga Dasysiphonia japonica (“siphoned Japan weed”) has been recorded at several sites within Scapa Flow and four locations in the Northern Isles. It was first recorded in 2015 and was common in 2016, mainly in scrape samples. It is considered a fairly new introduction to Orkney; it was first recorded by W. G. Sanderson in 2011, during a survey dive at Gutter Sound, Scapa Flow (specimens identified by C. Moore). The vector for the introduction to Europe from Japan is considered to be with Pacific oyster, Magallana gigas (Thunberg, 1793), importations (SjØtun et al. 2008) but, within Europe, dispersal has probably been partly through shipping movement (SjØtun et al. 2008). It was first recorded in the U.K. in 1999 at Milford Haven in Wales and in Scotland in 2004 at Alturlie Point, Moray Firth (SjØtun et al. 2008). Since then, it has been recorded in Loch Laxford, Sutherland in 2009 (Moore et al. 2010), Ullapool, Wester Ross in 2010 (Moore et al. 2011) and Shetland (Collin et al. 2015). Want et al. (2017) recorded it growing on renewable energy structures in Orkney. Published as part of Kakkonen, Jenni E., Worsfold, Tim M., Ashelby, Christopher W., Taylor, Andrea & Beaton, Katy, 2019, The value of regular monitoring and diverse sampling techniques to assess aquatic non-native species: a case study from Orkney, pp. 46-79 in Management of Biological Invasions 10 (1) on page 56, DOI:10.3391/mbi.2019.10.1.04, http://zenodo.org/record/11969078